2021
DOI: 10.1007/s13312-021-2213-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Sarcopenia in Survivors of Childhood Acute Lymphoblastic Leukemia

Abstract: Objective To describe the prevalence of obesity and sarcopenia among survivors of childhood acute lymphoblastic leukemia (ALL) using DEXA scan, and study associated risk factors. Methods This case control study was conducted between July, 2013 and June, 2014 at a tertiary care cancer centre in India. Study participants included 65 survivors of childhood ALL who were <18 years of age at diagnosis, treated between years 1996 and 2008, and were at least two years since com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Metabolic syndrome and altered body composition are emerging chronic health issues among Indian survivors of childhood cancer. 10,21 In our cohort, survivors with diagnoses of retinoblastoma, brain tumor, and nasopharyngeal carcinoma had the highest cumulative incidence of late effects grade 3 and above, possibly because of the large proportion of patients who underwent radiation and enucleation (in retinoblastoma) and use of cranial-directed radiotherapy in the others. Similarly, a high proportion of bone tumors underwent surgeries such as amputation and chemotherapy with alkylating agent and anthracyclines.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Metabolic syndrome and altered body composition are emerging chronic health issues among Indian survivors of childhood cancer. 10,21 In our cohort, survivors with diagnoses of retinoblastoma, brain tumor, and nasopharyngeal carcinoma had the highest cumulative incidence of late effects grade 3 and above, possibly because of the large proportion of patients who underwent radiation and enucleation (in retinoblastoma) and use of cranial-directed radiotherapy in the others. Similarly, a high proportion of bone tumors underwent surgeries such as amputation and chemotherapy with alkylating agent and anthracyclines.…”
Section: Discussionmentioning
confidence: 78%
“…Metabolic syndrome and altered body composition are emerging chronic health issues among Indian survivors of childhood cancer. 10 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, SO has been most commonly studied in children with acute lymphocytic leukemia (ALL). The findings show a frequent occurrence of SO during treatment and even years after survival [105][106][107][108]. Children with hematologic malignancies had more significant increases in fat mass than children with solid organ tumors [68].…”
Section: Sarcopenic Obesitymentioning
confidence: 82%
“…Several studies showed that CCS are prone to an excessive weight gain than their peers, due to glucocorticoids treatment, increased rate of hormonal dysfunction, excessive dietary intake, and a low level of physical exercise [4,5,36]. The prevalence of overweight and obesity in the previous published cohorts of CCS differs widely, according to age, follow-up duration, ethnicity, and social factors, as well as the prevalence of obesity in the general population of each country [37,38]. In our series, the prevalence of overweight (26.2%) and obesity (11.1%) was higher than indicated in the 2019 report of the Italian National Institute of Statistics (ISTAT) for the general population of the same age and country (15.8% and 3.0%, respectively), thus confirming the already reported tendency to overweight of childhood cancer survivors [39].…”
Section: Discussionmentioning
confidence: 99%